The question is saying a number is square, then squared again, and finally square again, making that number squared itself up to 3 times. So we take 6561 and we square root it 3 times. Square root of 6561 is 81, square of 81 is 9, and finally square root if 9 is 3. The final answer is 3.
Step-by-step explanation:
Hey there!
Given;
Slope (m) = -3/5
And passes through the point(4,-4).
Now; The equation of a line in slope intercept form is y= mx+b.
So, try to bring it in y= mx+b form.
Firstly let's use one-point formula.
![(y - y1) = m(x - x1)](https://tex.z-dn.net/?f=%28y%20-%20y1%29%20%3D%20m%28x%20-%20x1%29)
Now, keep all values.
![(y + 4) = \frac{ - 3}{5} (x - 4)](https://tex.z-dn.net/?f=%28y%20%2B%204%29%20%3D%20%20%5Cfrac%7B%20-%203%7D%7B5%7D%20%28x%20-%204%29)
Now, simplify to get answer.
![5(y + 4) = - 3(x - 4)](https://tex.z-dn.net/?f=5%28y%20%2B%204%29%20%3D%20%20-%203%28x%20-%204%29)
![5y + 20 = - 3x + 12](https://tex.z-dn.net/?f=5y%20%2B%2020%20%3D%20%20-%203x%20%2B%2012)
![5y = - 3x + 12 - 20](https://tex.z-dn.net/?f=5y%20%3D%20%20-%203x%20%2B%2012%20-%2020)
![5y = - 3x - 8](https://tex.z-dn.net/?f=5y%20%3D%20%20-%203x%20-%208)
![y = \frac{ - 3}{5} x - \frac{8}{5}](https://tex.z-dn.net/?f=y%20%3D%20%20%5Cfrac%7B%20-%203%7D%7B5%7D%20x%20-%20%20%5Cfrac%7B8%7D%7B5%7D%20)
Therefore the equation is y = -3/5x - 8/5.
<em><u>Hop</u></em><em><u>e</u></em><em><u> it</u></em><em><u> helps</u></em><em><u>.</u></em><em><u>.</u></em><em><u>.</u></em>
1.Each method works differently the angles inside them is what matters.
2. <span> Manipulating algebra tiles can help people solve linear equations
3.</span><span>Distribute each term of the first polynomial to every term of the second polynomial. Remember that when you multiply two terms together you must multiply the coefficient (numbers) and add the exponents. But with Integers you multiply two integers with different signs
4.So you know how </span>
A monomial is a number, a variable or a product of a number and a variable.
<span>multiply each term in one polynomial by each term in the other <span>polynomial
Examples:
![3x2(4x2 – 5x + 7) –6xy(4x2 – 5xy – 2y2) (3x – 4y)(5x – 2y) (4x – 5)(2x2 + 3x – 6)](https://tex.z-dn.net/?f=3x2%284x2%20%E2%80%93%205x%20%2B%207%29%0A%20%E2%80%936xy%284x2%20%E2%80%93%205xy%20%E2%80%93%202y2%29%0A%283x%20%E2%80%93%204y%29%285x%20%E2%80%93%202y%29%0A%284x%20%E2%80%93%205%29%282x2%20%2B%203x%20%E2%80%93%206%29)
</span></span>
Answer: One possible way: 123 - 45 - 67 + 89
Step-by-step explanation: The goal is to get 100, using all of the following numbers: (1,2,3,4,5,6,7,8,9)
We can merge numbers to get 100.
123 - 45 - 67 + 89 (We used every number once)
Lets solve from left to right.
123 - 45 = 78. 78 - 67 = 11. 11 + 89 = 100.